2015
DOI: 10.4103/0974-7753.171573
|View full text |Cite
|
Sign up to set email alerts
|

A marine protein-based dietary supplement for subclinical hair thinning/loss: Results of a multisite, double-blind, placebo-controlled clinical trial

Abstract: Introduction:Since skin and hair quality are potent vitality signals, and hair growth deficiency can cause significant psychological morbidity. In addition to clearly-defined hair loss disorders, milder forms of hair thinning or hair loss appear to be increasingly common, with a suggestion that sub-optimal diets and stressful lifestyles may be involved.Methods:Here we assess the value of a dietary marine-extract based dietary supplement in premenopausal women with subclinical hair thinning or hair loss conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 37 publications
1
32
0
Order By: Relevance
“…The initial reduction was because the villus hair had converted to terminal hair while the later rise was due to new hair growth induced with the treatment cycle and the counts finally stabilize as per the individual hair cycle and the individual turnover of hair fall and hair growth. Rizer et al [70] reported improvement in thickness of villus hair in 60% patients in their marine protein supplement study. Nicholas et al…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The initial reduction was because the villus hair had converted to terminal hair while the later rise was due to new hair growth induced with the treatment cycle and the counts finally stabilize as per the individual hair cycle and the individual turnover of hair fall and hair growth. Rizer et al [70] reported improvement in thickness of villus hair in 60% patients in their marine protein supplement study. Nicholas et al…”
Section: Discussionmentioning
confidence: 99%
“…Rizer et al [70] who studied the benefit of marine protein supplement reported 20% reduced hair shedding within 4 months, while the placebo group had increased shedding by 50%. Hair loss in control group continued the same in 41% and increased in 37% patients at the end of 4 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two recent trials by Ablon and colleagues [50,51] reported a significant improvement in hair counts and hair volume with the use of oral marine protein supplement (MPS). Using oral MPS 3 times daily in 100 females with self-perceived hair loss for 6 months demonstrated a significant increase in the mean hair diameter of vellus-like hairs, as well as a reduction in shedding [50].…”
Section: Marine Proteinsmentioning
confidence: 99%